2016
DOI: 10.1111/ecc.12487
|View full text |Cite
|
Sign up to set email alerts
|

The effects of a cancer diagnosis on the health of a patient's partner: a population-based registry study of cancer in Sweden

Abstract: The aim of this population-based registry study was to explore how cancer influences the health of partners, by examining the onset of new diagnoses for partners, health care use and health care costs among partners living with patients with cancer. The sample consisted of partners of patients with cancer (N = 10 353) and partners of age- and sex-matched controls who did not have cancer (N = 74 592). Diagnoses, health care use and health care costs were studied for a continuous period starting 1 year before th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
27
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(27 citation statements)
references
References 46 publications
0
27
0
Order By: Relevance
“…The stress that partners are exposed to may depend on the cancer type and related symptom severity and prognosis. 1 We have previously shown that men whose partner was diagnosed with breast cancer had an increased risk of being hospitalized with an affective disorder (HR, 1.39; 95% CI, 1.20-1.61) 36 and modestly elevated risk of prescription of anti-depressant medication (HR = 1.08; 95% CI, 1.03-1.13). 37 In addition to a life-threatening disease in their loved one, partners of glioma patients also experience extensive caregiving tasks, 2 a drastic decline in patients' function, and loss of the emotional and intimate connection with their partner due to changes in cognitive function and personality.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…The stress that partners are exposed to may depend on the cancer type and related symptom severity and prognosis. 1 We have previously shown that men whose partner was diagnosed with breast cancer had an increased risk of being hospitalized with an affective disorder (HR, 1.39; 95% CI, 1.20-1.61) 36 and modestly elevated risk of prescription of anti-depressant medication (HR = 1.08; 95% CI, 1.03-1.13). 37 In addition to a life-threatening disease in their loved one, partners of glioma patients also experience extensive caregiving tasks, 2 a drastic decline in patients' function, and loss of the emotional and intimate connection with their partner due to changes in cognitive function and personality.…”
Section: Discussionmentioning
confidence: 98%
“…Our results support previous studies that found elevated self‐reported mood symptoms such as depression and anxiety in partners of glioma patients, but further add to the existing literature by showing that partners of glioma patients are exposed to stress so severe that they are at increased risk for psychiatric symptoms (eg, severe anxiety and sleep problems) warranting prescription of psychotropic medication. The stress that partners are exposed to may depend on the cancer type and related symptom severity and prognosis . We have previously shown that men whose partner was diagnosed with breast cancer had an increased risk of being hospitalized with an affective disorder (HR, 1.39; 95% CI, 1.20‐1.61) and modestly elevated risk of prescription of anti‐depressant medication (HR = 1.08; 95% CI, 1.03–1.13) .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…26 A plausible suggestion for gendered differences might also be that not only people's help-seeking behaviour but also health personnel's referrals are influenced by norms and ideas of men as stoic and women as help-seeking, 27,28 ie, that women are more inclined and more often encouraged to engage in psychosocial support while distressed and that men might seek other types of support. For example, a recent Swedish study 29 shows that in cases of mood disorders and severe stress, male more than female partners are prone to seek traditional health care, which might indicate that men tend to look for medical care with "strong backs" rather than psychosocial support with "soft fronts" when distressed. 30 In total, almost half of the motives concerned help in dealing with personal grief connected to the patient's cancer and distressing symptoms (categories 1 and 3).…”
Section: Discussionmentioning
confidence: 99%
“…Möllerberg et al. () also explored the issue of partners in their Swedish registry‐based study. It is important for health care providers to be attuned to the needs of partners, and to acknowledge that a diagnosis of cancer in a partner can have adverse health effects.…”
mentioning
confidence: 99%